Lima commitment. Conference of Ministers of Foreign Affairs and Defense of the Andean Community - Andina, Comunidad (2016)
The Ministers of Foreign Affairs and Defense of Bolivia, Colombia, Ecuador, Peru and Venezuela, gathered in the city of Lima in order to analyze the proposal of President Alejandro Toledo to promote a common conception of security, peace, improvement and the extension of confidence-building measures, as well as the implementation of initiatives aimed at promoting the limitation of expenses for external defense.